2019
DOI: 10.1177/2055116919885699
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of feline urolithiasis in Mexico (2006–2017)

Abstract: ObjectivesThe objectives of this study were to identify the proportions of different types of uroliths, characterize the population of cats that present with urolithiasis and determine possible predisposing factors in a population of Mexican cats.MethodsThis study analyzed clinical specimens of feline urolithiasis submitted to our laboratory in the period from 2006 to 2017. The mineral composition of the uroliths was determined by qualitative and quantitative mineral analyses, performed by stereoscopic microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
1
9
0
3
Order By: Relevance
“…In agreement with previous epidemiologic studies, struvite and CaOx uroliths were the most prevalent uroliths in cats, overall representing 87.8% of the urolith submissions in the present study [ 1 , 2 , 10 – 13 ]. Unfortunately, sample size was too small to detect any changes in proportions of urolith composition over the study period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous epidemiologic studies, struvite and CaOx uroliths were the most prevalent uroliths in cats, overall representing 87.8% of the urolith submissions in the present study [ 1 , 2 , 10 – 13 ]. Unfortunately, sample size was too small to detect any changes in proportions of urolith composition over the study period.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that the two most common types of uroliths in cats are calcium oxalate (CaOx) and magnesium ammonium phosphate (struvite) [ 1 , 2 , 10 – 13 ]. In cats, struvite was the most common type of urolith during the early 1980s, representing 78% of the uroliths submitted to the Minnesota Urolith Center (MUC) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Independentemente do tipo de urólito encontrado, as idades com maior predisposição e ocorrência de casos não condizem com a presenciada no atual relato, onde o paciente felino apresentava urolitíase de fosfato de cálcio com 2 meses de idade. Felinos adultos jovens, em torno de 1 a 6 anos, tendem a desenvolver urolitíase por fosfato triplo, enquanto felinos com idade superior, de 7 a 10 anos, tendem a ser mais predispostos a formar cálculos de oxalato de cálcio (Mendoza-López et al, 2019). O paciente deste relato apresentava urolitíase de fosfato de cálcio e o urólito principal apresentava tamanho de 2,0 x 2,0 x 4,5 mm, pesando 0,007 gramas.…”
Section: Resultsunclassified
“…Em 2006, os urólitos de estruvita representaram 50% e os de oxalato de cálcio 39% nas avaliações realizadas, no entanto ocorreu uma alternância em 2019, onde 54% dos urólitos relatados foram compostos de oxalato de cálcio e apenas 32% compostos por estruvita. De maneira mais infrequente encontrou-se os demais constituintes de cristais, como sílica, urato, cistina e fosfato de cálcio (Mendoza-López et al, 2019). Ressaltando o componente atípico presente no urólito do relato em questão, o fosfato de cálcio, o qual em diferentes estudos apresentou uma prevalência menor que 1% (Gomes et al, 2018).…”
Section: Resultsunclassified
“…Автор с сожалением констатирует, что в настоящее время для большинства регионов РФ эпидемиологическая статистика заболеваемости домашних животных уролитиазом недоступна. В зарубежных странах, в частности в Европейском [19,20,23,25] и Азиатском регионе [28], странах Американского континента [21,26,27] и Африки [29] регулярно публикуются многочисленные исследования, посвященные эпидемиологии FLUTD и уролитиазу кошек. Автор надеется, что проблеме эпидемиологии уролитиаза домашних животных, в том числе кошек, в РФ будет уделяться больше внимания со стороны практикующих ветеринарных врачей и исследователей.…”
Section: Introductionunclassified